Humanist formation: The role of literary reading in the performance of the school librarian - Sala, Fabiana; de Castro Filho, Cláudio Marcondes; de Almeida Junior, Oswaldo Francisco [UNESP] (Universidade Estadual de Campinas, 2021)
Introduction: Literary reading is considered one of the most relevant activities for the improvement of interpersonal skills, such as empathy, considered essential in performing the functions of the school librarian. Objective: Thus, this study aims to discuss how the practice of literary reading can influence the performance of the school librarian from the perspective presented by the author Carlos Ruiz Záfon in the plot of his work A Sombra do Vento. Method: Regarding methodological procedures, this is a qualitative research, which had as scientific method the use of bibliographic research and the questionnaire as a data collection instrument. Results: The results show that librarians are aware of the importance of literary reading for the performance of their professional activities and for the construction of a more empathic and humanistic relationship with students, but this practice is not often discussed frequently in research in the area and encouraged in undergraduate courses. Conclusion: However, it is expected that the present study can contribute to the debates on the subject in the area of Information Science and reflect on the influence of literary reading for a more humanistic and empathic formation of the school librarian.
Formação humanista: O papel da leitura literária na atuação do bibliotecário escolar
Keywords: Literary reading; Professional performance; Reading practices; School librarian